As contribuições do Sistema de Gestão de Incentivos Fiscais da SUDAM a partir de uma análise com base na teoria sistêmica para o desenvolvimento regional: um estudo de caso na Amazônia Legal - SILVA FILHO, Luzio Santana da Silva (Universidade Federal do Pará, 2023)
This study investigates the contributions of the implementation of a Management Information System, called Tax Incentive Management System - SIN, within the scope of the Amazon Development Superintendence - SUDAM, whose starting position was a holistic analysis of the situation. The study's general objective is to analyze the contributions of the SIN to regional development, in the context of document processing, in the SUDAM tax incentive process and uses the Systemic Theory as a basis. It has as field research the application of questionnaires, being a structured one in which the Likert Scales were used to evaluate the perception of the users of the system in aspects that involve the Support, Usability and Efficiency. In addition, a semi-structured interview was applied to SUDAM employees and a document analysis was carried out on the subject. As a result, from the perspective of tax incentive technicians, the SIN presents as positive highlights the themes of Support and Support for users, in addition to providing an improvement in the Efficiency of the works, while presenting as an opportunity for improvement a large space for the evolution of the Usability of the system. Still composing the results, there was a great alignment between the PRDA and PDTIC documents and an expressive trend of improvement in procedural indicators was identified in the Management Reports.